Solid catalyst component for olefin polymerization and preparation method and application thereof

By changing the composition and structure of the active center and using specific internal electron donor compounds for prepolymerization, the problem of insufficient hydrogen regulation sensitivity of the catalyst is solved, and the processing performance of the polymer is improved.

CN119798490APending Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311309982.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing catalysts used for olefin polymerization have insufficient hydrogen adjustment sensitivity, resulting in a high fine powder content in the polymer and affecting the processing performance of the product.

Method used

By changing the composition and structure of the active center, specific internal electron donor compounds, such as compounds in formula (I), and through special prepolymerization methods, the hydrogen adjustment sensitivity of the catalyst is improved while increasing the bulk density and width of the molecular weight distribution.

Benefits of technology

It improves the hydrogen adjustment sensitivity of the catalyst, reduces the fine powder content in the polymer, and enhances the processing performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798490A_ABST
    Figure CN119798490A_ABST
Patent Text Reader

Abstract

The invention provides a solid catalyst component for olefin polymerization and a preparation method and application thereof, and belongs to the technical field of olefin polymerization. The catalyst component comprises a magnesium element, a titanium element, halogen, poly-alpha-olefin and an internal electron donor compound; the internal electron donor compound comprises a compound as shown in a formula (I). The catalyst has high hydrogen regulation sensitivity and high bulk density, the molecular weight distribution of the product is wider, and the processability of the product is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of olefin polymerization catalysts, and in particular to a solid catalyst component for olefin polymerization and a preparation method and application thereof. Background Art

[0002] Polypropylene is widely used and is one of the five major synthetic resins. It has achieved rapid development in the past decade, which is mainly the result of the continuous development of catalyst technology and processing technology. Its catalysts can be divided into single-active center catalysts and Ziegler-Natta catalysts. The latter is mainly used in today's industry. A notable feature of this type of catalyst is the existence of morphology replication. This morphology replication can be beneficial to the fluidity of the polymer and the fluidity of the catalyst. For example, if the catalyst is prepared into a spherical catalyst, a spherical polymer with good fluidity may be obtained. Because of these advantages of spherical catalysts, industrial annular polypropylene process units basically use this type of catalyst. The application of spherical catalysts in these process units must first be prepolymerized at low temperature in the prepolymerization unit before the final polymer can replicate the morphology of the catalyst. In addition, there is still a phenomenon of catalyst particles and polymer particles being broken in the production of the resin, resulting in a high content of fine powder in the polymer. If prepolymerization is not performed, the catalyst or polymer particles are basically broken during the polymerization process, and the advantages of the spherical catalyst are lost. Therefore, many researchers have carried out research.

[0003] For example, US9453088B2 discloses a prepolymerization catalyst using a spherical catalyst containing two electron donors, 1,3-diether and aromatic ester, and prepolymerizing olefins of 2 to 10 carbon atoms to obtain a prepolymerization catalyst having an average particle size of less than 30 μm and a prepolymerization multiple of less than 50. US7329714B2 discloses a prepolymerization method using a catalyst and propylene or 4-methyl-1-pentene to polymerize at 0 to 40°C.

[0004] The purpose of the above-mentioned prepolymerized catalysts is to reduce the breakage phenomenon and the content of polymer fine powder, but there is still the problem of insufficient catalyst hydrogen sensitivity. Summary of the invention

[0005] The purpose of the present invention is to provide a solid catalyst component for olefin polymerization, a preparation method and an application thereof. The solid catalyst component of the present invention overcomes the problem of insufficient hydrogen adjustment sensitivity of the existing catalyst using the compound of formula (I) as an internal electron donor by changing the composition and structure of the active center. After the catalyst is prepolymerized by a special method, the hydrogen adjustment sensitivity of the catalyst can be improved. At the same time, the catalyst has a higher bulk density and a wider product molecular weight distribution, which is beneficial to improving the processing performance of the product.

[0006] According to a first aspect of the present invention, the present invention provides a solid catalyst component for olefin polymerization, comprising magnesium, titanium, halogen, poly-α-olefin and an internal electron donor compound, wherein the internal electron donor compound comprises a compound represented by formula (I):

[0007]

[0008] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 of aralkyl.

[0009] According to a second aspect of the present invention, the present invention provides a method for preparing a solid catalyst component for olefin polymerization, comprising:

[0010] (1) In the presence of an inert solvent, a catalyst component A, an alkyl aluminum and an external electron donor compound are contacted and reacted; the catalyst component A contains titanium, magnesium, a halogen and an internal electron donor compound; the internal electron donor compound includes a compound represented by formula (I):

[0011]

[0012] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C10 Alkyl or C7~C 10 Aralkyl;

[0013] (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction;

[0014] (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

[0015] The mass ratio of the α-olefin to the catalyst component A is 0.04:1 to 10:1, and the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa.

[0016] According to the third aspect of the present invention, the present invention provides a solid catalyst component prepared by the method described in the second aspect of the present invention.

[0017] According to a fourth aspect of the present invention, the present invention provides a catalyst for olefin polymerization, the catalyst comprising the solid catalyst component according to the first or third aspect of the present invention, an alkyl aluminum and an optional external electron donor compound or a reaction product thereof.

[0018] According to a fifth aspect of the present invention, there is provided a method for olefin polymerization, the method comprising: subjecting olefin to a polymerization reaction in the presence of the catalyst for olefin polymerization.

[0019] The catalyst containing the compound of the specific formula (I) of the present invention can improve the hydrogen sensitivity of the catalyst after prepolymerization by a special method. At the same time, the catalyst has a higher bulk density and a wider molecular weight distribution of the product, which is beneficial to improving the processing performance of the product. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0021] According to a first aspect of the present invention, the present invention provides a solid catalyst component for olefin polymerization, comprising magnesium, titanium, halogen, poly-α-olefin and an internal electron donor compound, wherein the internal electron donor compound comprises a compound represented by formula (I):

[0022]

[0023] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C10 Alkyl or C7~C 10 Aralkyl;

[0024] R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0025] Wherein, the R'1 and R'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl or aralkyl groups are optionally replaced by other atoms.

[0026] Optionally, the poly-α-olefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene and polyisoprene, preferably polypropylene.

[0027] Optionally, based on the total weight of the catalyst component, the content of magnesium in the catalyst component is 1 weight % to 18 weight %, the content of titanium is 0.1 weight % to 3.5 weight %, the content of halogen is 2 weight % to 65 weight %, the content of poly-α-olefin is 0.1 weight % to 89 weight %, and the content of internal electron donor compound is 0.6 weight % to 15 weight %.

[0028] In some specific embodiments, based on the total mass of the catalyst component, the solid catalyst component contains 0.1 to 89 weight % of poly-α-olefin, 0.1 to 3.5 weight % of titanium, 1 to 18 weight % of magnesium, 2 to 65 weight % of chlorine and 0.6 to 15 weight % of internal electron donor compound; preferably, based on the total weight of the catalyst component, the content of the poly-α-olefin is 1 to 50 weight %, the content of the titanium is 0.5 to 2.5 weight %, the content of the magnesium is 1 to 16 weight %, the content of the chlorine is 2 to 55 weight %, and the content of the internal electron donor compound is 1 to 10 weight %.

[0029] In some specific embodiments, based on the total weight of the catalyst component, the content of the poly-α-olefin is 9.5-35 weight %, the content of the titanium element is 1.5-2.5 weight %, the content of the magnesium element is 11-16 weight %, the content of the chlorine element is 40-55 weight %, and the content of the internal electron donor compound is 8-10 weight %.

[0030] Optionally, the catalyst component is spherical solid particles.

[0031] Optionally, the average particle size D of the catalyst component 50 The average particle size D of the solid catalyst component is 5 to 150 μm, preferably 20 to 80 μm. 50 The thickness may be 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 100 μm, 120 μm, 150 μm or a range consisting of these.

[0032] Optionally, the halogen in the present invention is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine.

[0033] Optionally, the magnesium element comes from alkoxymagnesium, spherical magnesium chloride alcoholate or spherical magnesium compound.

[0034] Optionally, the general formula of the magnesium alkoxide is Mg(OEt) 2-k-l (OEH) k (OiPr) l , wherein Et is ethyl, EH is 2-ethylhexyl, iPr is isopropyl, and k and l are each independently 0 to 0.5.

[0035] Optionally, the general formula of the spherical magnesium chloride alcoholate is Mg(R′OH) i (H2O) j , wherein R′ is methyl, ethyl, n-propyl or isopropyl, i is 1.5 to 3.5, and j is 0 to 0.1.

[0036] Optionally, the general formula of the spherical magnesium compound is as shown in formula (II):

[0037]

[0038] In formula (II), R1 is C1~C 12 R2 and R3 are the same or different and are hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen; m is 0.1-1.9; n is 0.1-1.9; m+n=2.

[0039] In the present invention, the average particle size D 50 The particle size was measured using Master Sizer 2000 laser particle size analyzer (manufactured by Malvern Instruments Ltd).

[0040] According to the solid catalyst component provided by the present invention, the titanium content can be measured according to the colorimetric method. Specifically, 0.2-0.5 g of the sample is dissolved in 50 mL of 2N H2SO4, the upper floating matter is filtered, and the clear liquid is taken for colorimetry; 2N H2SO4 solution is used as a blank, the thickness of the cuvette is 1 cm, and the absorbance E1 is measured at a wavelength of 410 μm, and then 1 drop of 30% H2O2 is dripped, shaken, and the absorbance E2 is measured, and the titanium content Ti (%) is calculated according to the following formula:

[0041] Ti%=[(E2-E1)×100) / (K·L·W·100)]×100

[0042] Where: W is sample weight (g); L is cuvette thickness (cm); K is specific extinction coefficient; E1 is blank absorbance; E2 is sample absorbance.

[0043] The magnesium content can be measured according to the EDTA titration method. Specifically, take 0.2-0.5g of the sample in a 250mL conical flask, add 20-30mL 2N H2SO4 solution to dissolve, add 20mL triethanolamine (1+2) standard solution, adjust pH=10 with 20% NaOH solution, shake, add 10mL pH=10 buffer solution, add 6 drops of 30% H2O2 and 30-50mL distilled water, add a small amount of chrome black T indicator, shake well, titrate with 0.02N EDTA solution until the color changes from purple-red to blue (purple light disappears) as the end point, and calculate the magnesium content Mg (%) according to the following formula:

[0044] Mg(%)=[(VE·NE×24.31) / (G·1000)]×100

[0045] In the formula: G is the sample mass (g); VE is the amount of EDTA consumed (mL); NE is the equivalent number of EDTA solution; 24.31 is the atomic weight of magnesium.

[0046] The chlorine content can be measured by silver nitrate titration. Specifically, weigh 0.04-0.1g of sample into a conical flask, add 20mL of 2N H2SO4 solution, and let it stand for 30 minutes; after rinsing with distilled water several times, add 20-30mL of 0.1N AgNO3 solution, add 3mL of 1:1 HNO3 solution, and titrate the excess AgNO3 solution with 0.1N NH4CNS standard solution. Titrate until the brick red color does not disappear for two seconds as the end point, and calculate the chlorine content Cl (%) according to the following formula:

[0047] Cl(%)=[(V1-V2×D)×N1×35.45 / G·1000)]×100

[0048] In the formula: V1—amount of AgNO3 solution (mL); V2—amount of NH4CNS solution consumed (mL); D—volume ratio of AgNO3 / NH4CNS solution; N1—equivalent concentration of AgNO3; G—mass of sample (g); 35.45—atomic weight of chlorine.

[0049] The test method for the poly-α-olefin content in the solid catalyst component is as follows: weigh a certain amount of sample (M1) and dissolve it in ethanol and dilute hydrochloric acid, dry the insoluble matter at 80°C under vacuum to obtain a solid (M2), take 0.2g of the solid to make a tablet, measure the poly-α-olefin content (C1) of the solid by infrared spectrometer, and calculate the mass percentage of the poly-α-olefin in the solid catalyst component according to the following formulas:

[0050] C A =M2×C1 / M1

[0051] C A is the mass percentage of polyα-olefin in the solid catalyst component, M1 and M2 are the mass (g) of the sample and the dry solid, respectively, and C1 is the mass percentage of polyα-olefin in the dry solid.

[0052] The test method for the content of the internal electron donor compound in the solid catalyst component is: dissolve the sample with ethyl acetate and hydrochloric acid solution (concentration 2 mol / L), extract the internal electron donor compound, and analyze its content using a conventional liquid chromatograph.

[0053] According to the solid catalyst component provided by the present invention, the solid catalyst component further contains alkyl aluminum and an external electron donor. The types and contents of the alkyl aluminum and the external electron donor can be selected with reference to existing olefin prepolymerization catalysts.

[0054] In addition, the solid catalyst component of the present invention may contain other components, such as an inert solvent, in addition to the above components.

[0055] According to a second aspect of the present invention, the present invention provides a method for preparing a solid catalyst component for olefin polymerization, comprising:

[0056] (1) in the presence of an inert solvent, a catalyst component A, an alkyl aluminum and an external electron donor compound are contacted and reacted; the catalyst component A contains titanium, magnesium, a halogen and an internal electron donor compound; the internal electron donor compound includes a compound represented by formula (I);

[0057]

[0058] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0059] R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0060] Wherein, the R"'1 and R"'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen on the aromatic ring in the aryl, alkylaryl or aralkyl group is optionally replaced by other atoms;

[0061] (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction;

[0062] (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

[0063] Optionally, the preparation method provided by the present invention further comprises: (4) removing unreacted hydrogen, and sequentially performing solid-liquid separation and drying treatment on the system obtained in step (3) to obtain the solid catalyst component. In some preferred embodiments, the solid-liquid separation comprises filtering to remove the liquid, washing with hexane 1 to 2 times, and the drying treatment comprises vacuum drying, and the drying conditions include: a temperature of 10 to 80°C, preferably 40 to 50°C, and a time of 30 to 60 minutes. In the present invention, the vacuum drying can be implemented by a conventional vacuum pump, and the present invention has no special requirements for it.

[0064] Optionally, the α-olefin is selected from one or more of ethylene, propylene, butene, octene and isopentene, preferably propylene.

[0065] Optionally, the mass ratio of the α-olefin to the catalyst component A is 0.04: 1 to 10: 1. For example, the mass ratio of the α-olefin to the catalyst component A can be 0.04: 1, 0.05: 1, 0.08: 1, 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1 or a range thereof.

[0066] Optionally, the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa, preferably 0.1 to 0.5 MPa, and more preferably 0.2 to 0.3 MPa.

[0067] Optionally, in step (1), the contact reaction conditions include: temperature of 0 to 30° C., preferably 15 to 25° C.; time of 1 to 30 min, preferably 10 to 20 min.

[0068] Optionally, the conditions for the polymerization reaction in step (2) include: a temperature of 0 to 50° C., preferably 15 to 25° C.; and a time of 5 to 30 min, preferably 10 to 20 min.

[0069] Optionally, the reaction conditions in step (3) include: temperature of 0 to 50° C., preferably 15 to 25° C.; time of 5 to 30 min, preferably 10 to 20 min.

[0070] Optionally, the magnesium element comes from alkoxymagnesium, spherical magnesium chloride alcoholate or spherical magnesium compound.

[0071] Optionally, the general formula of the magnesium alkoxide is Mg(OEt) 2-k-l (OEH) k (OiPr) l , wherein Et is ethyl, EH is 2-ethylhexyl, iPr is isopropyl, and k and l are 0 to 0.5.

[0072] Optionally, the general formula of the spherical magnesium chloride alcoholate is Mg(R′OH) i (H2O) j , wherein R′ is methyl, ethyl, n-propyl or isopropyl, i is 1.5 to 3.5, and j is 0 to 0.1.

[0073] Optionally, the general formula of the spherical magnesium compound is as shown in formula (II):

[0074]

[0075] In formula (II), R1 is C1~C 12 R2 and R3 are the same or different and are hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen; m is 0.1-1.9; n is 0.1-1.9; m+n=2.

[0076] Optionally, according to the preparation method provided by the present invention, in step (1), the alkyl aluminum and the external electron donor compound can be selected with reference to the existing olefin prepolymerization catalyst, and the present invention has no particular limitation on this. Generally, the alkyl aluminum can be selected from one or more of triethyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, tri-n-hexyl aluminum and diethyl aluminum monochloride. The external electron donor compound can be selected from one or more of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane and dicyclopentyldimethoxysilane.

[0077] Generally, the molar ratio of the alkyl aluminum, the external electron donor compound and the amount of the catalyst component A calculated as titanium element can be 1 to 50: 0.2 to 10: 1. For example, the molar ratio of the alkyl aluminum, the external electron donor compound and the amount of the catalyst component A calculated as titanium element can be 1: 0.2: 1, 5: 0.2: 1, 10: 0.2: 1, 15: 0.2: 1, 20: 0.2: 1, 30: 0.2: 1, 40: 0.2: 1, 50: 0.2: 1, 15: 0.3: 1, 15: 0.5: 1, 15: 1: 1, 15: 2: 1, 15: 3: 1, 15: 4: 1, 15: 5: 1, 15: 20: 1 or any range of values ​​of the alkyl aluminum and the external electron donor compound in the above ratios.

[0078] Optionally, according to the preparation method provided by the present invention, in step (1), the inert solvent can be selected with reference to the prior art. Generally, the inert solvent can be selected from one or more of hexane, heptane and decane. The amount of the inert solvent added is such that the mass concentration of the catalyst component A in the inert solvent can be 5 to 50 g / L.

[0079] Optionally, according to the preparation method provided by the present invention, hydrogen can be added in the form of pure hydrogen or a hydrogen mixture. Preferably, the hydrogen mixture consists of hydrogen and an inert gas, and more preferably, the inert gas is selected from at least one of nitrogen, helium, neon and argon. The present invention has no special requirements for the concentration of hydrogen in the hydrogen mixture, as long as the defined reaction pressure can be achieved.

[0080] According to the preparation method provided by the present invention, the catalyst component A can be prepared according to the conventional method of the main catalyst in the olefin polymerization catalyst in the art, and the present invention is not particularly limited to this. For example, it can be prepared by referring to the methods disclosed in patent applications WO2012034357A1, WO2012097680A1 and patents ZL03153152.0, ZL200410062291.3, ZL201310491641.7, ZL201310491393.6 and ZL201310491648.9.

[0081] In the present invention, the catalyst component A may be a reaction product comprising titanium tetrachloride, a carrier and an internal electron donor compound, and the carrier is preferably an alkoxy magnesium carrier, a magnesium chloride alcoholate spherical carrier or a spherical magnesium compound carrier.

[0082] In the present invention, the average particle size of the carrier is 5 to 150 μm, more preferably 20 to 80 μm, and more preferably 30 to 60 μm.

[0083] In some embodiments, the catalyst component A can be prepared by referring to the methods disclosed in patents ZL03153152.0 and ZL200410062291.3. More specifically, the carrier is a spherical carrier of magnesium chloride alcoholate, and the catalyst component A is the reaction product of titanium tetrachloride, spherical magnesium chloride alcoholate and the internal electron donor compound such as carboxylic acid ester.

[0084] The general formula of the spherical magnesium chloride alcoholate can be Mg(R′OH) i (H2O) j , wherein R′ is methyl, ethyl, n-propyl or isopropyl, i is 1.5 to 3.5, and j is 0 to 0.1.

[0085] The catalyst component A is prepared by a method comprising the following steps:

[0086] 1) reacting titanium tetrachloride with the magnesium chloride alcoholate spherical carrier at -20°C to 0°C for 20 to 120 minutes to obtain a mixture I;

[0087] 2) heating the mixture I to 100-120° C., adding the internal electron donor compound such as carboxylic acid ester during the heating process, and reacting at 100-120° C. for 20-200 min to obtain a solid product II;

[0088] 3) The solid product II is washed with titanium tetrachloride and hexane respectively and then vacuum dried.

[0089] In some other embodiments, the catalyst component A can be prepared by referring to the methods disclosed in patents ZL201310491641.7, ZL201310491393.6 and ZL201310491648.9. More specifically, the carrier is a spherical magnesium compound carrier, and the catalyst component A is a reaction product of titanium tetrachloride, a spherical magnesium compound carrier and the internal electron donor compound such as carboxylic acid ester.

[0090] According to the preparation method provided by the present invention, the vacuum drying conditions in the above operation include: temperature of 40-50°C and time of 30-60 min. In the present invention, the vacuum drying can be implemented by a conventional vacuum pump, and the present invention has no special requirements for it.

[0091] According to the third aspect of the present invention, the present invention provides a solid catalyst component prepared by the preparation method described in the second aspect of the present invention.

[0092] According to a fourth aspect of the present invention, the present invention provides a catalyst for olefin polymerization, which comprises the solid catalyst component of the present invention, an alkyl aluminum and an optional external electron donor compound or a reaction product thereof.

[0093] According to the catalyst provided by the present invention, the alkyl aluminum, the external electron donor compound and their respective contents can be selected according to the prior art.

[0094] Generally, the alkylaluminum can be selected from one or more of triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum and diethylaluminum monochloride.

[0095] Optionally, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the solid catalyst component calculated as titanium element may be 1 to 1000: 1. For example, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the solid catalyst component calculated as titanium element may be 1: 1, 2: 1, 5: 1, 10: 1, 20: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1 or a range thereof.

[0096] Generally, the external electron donor compound can be selected from at least one of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane, cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane and tert-hexyltrimethoxysilane.

[0097] Optionally, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the external electron donor compound calculated as silicon element is 2 to 1000: 1. For example, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the external electron donor compound calculated as silicon element can be 2: 1, 5: 1, 10: 1, 20: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1 or a range thereof.

[0098] According to a fifth aspect of the present invention, there is provided a method for olefin polymerization, the method comprising: subjecting olefin to polymerization reaction in the presence of the catalyst for olefin polymerization according to the fourth aspect of the present invention.

[0099] According to the method provided by the present invention, the general formula of the olefin is CH2=CHR, R is hydrogen, C1-C6 alkyl or C6-C 10 Preferably, the olefin is selected from one or more of ethylene, propylene, butene, pentene and hexene.

[0100] According to the method provided by the present invention, the conditions of the polymerization reaction can be conventionally selected in the art, for example, the reaction temperature is 0 to 150° C., preferably the reaction temperature is 60 to 90° C., and the reaction pressure is normal pressure or higher pressure.

[0101] The advantages of the technical solution of the present invention will be described in detail below through specific embodiments.

[0102] In the following examples and comparative examples,

[0103] The isotactic index of a polymer (polypropylene) refers to the mass percentage of the polymer that is insoluble in boiling n-heptane under specified conditions. It is determined by the heptane extraction method (6 hours of boiling heptane extraction), i.e., 2 g of a dry polymer sample is taken, placed in an extractor and extracted with boiling heptane for 6 hours, and then the residue is dried to constant weight. The ratio of the mass (g) of the obtained polymer to 2 is the isotactic index.

[0104] The polymer melt index is measured according to the method of ASTM D1238-99.

[0105] In the following embodiments, unless otherwise specified, the "vacuum" refers to the vacuum degree achieved by a conventional vacuum pump.

[0106] The following preparation example is used to illustrate the preparation method of catalyst component A.

[0107] Preparation Example 1

[0108] In a 300 ml glass reaction bottle with stirring, add 120 ml titanium tetrachloride and cool to -20 °C. Then, under stirring, add 100 g of magnesium chloride alcoholate spherical carrier [Mg(C2H5OH)2.5 ](average particle size D50=40μm), react at -20℃ for 0.5 hour, then slowly heat up to 120℃, add 15g of diethyl 2,3-diisopropyl-2-cyanosuccinate during the heating process, then react at 120℃ for 0.5 hour, filter out the liquid, add 120ml of titanium tetrachloride and wash twice, wash the obtained solid product with hexane 5 times, and finally dry in vacuo at 45℃ to obtain catalyst component A-1.

[0109] Preparation Example 2

[0110] In a 300 ml glass reaction bottle with stirring, add 120 ml titanium tetrachloride and cool to -20 °C. Then, under stirring, add 100 g of magnesium chloride alcoholate spherical carrier [Mg(C2H5OH) 2.6 ](average particle size D50=42μm), react at -20℃ for 0.5 hour, then slowly heat up to 120℃, add 15g of diethyl 2,3-diisopropyl-2-cyanosuccinate during the heating process, then react at 120℃ for 0.5 hour, filter out the liquid, add 120ml of titanium tetrachloride and wash twice, wash the obtained solid product with hexane 5 times, and finally dry in vacuo at 45℃ to obtain catalyst component A-2.

[0111] Preparation Example 3

[0112] In a 2L reactor, add 40g (0.4mol) of magnesium chloride, 280mL (4.8mol) of ethanol, 5g of ethyl acetate, and 5g of PVP (polyvinylpyrrolidone) as surfactants, heat to 90°C with stirring, react at this temperature for 2 hours, then add 190mL (2.4mol) of epichlorohydrin, continue to react at this temperature at 90°C for half an hour, then filter press, wash the filter press product with toluene 8 times, and finally dry the product in vacuum to obtain a spherical catalyst carrier Z1 for olefin polymerization.

[0113] The average particle diameter (D50) of the olefin polymerization catalyst spherical carrier Z1 is 56 microns, and the particle size distribution ((D90-D10) / D50) is 1.0. The particle morphology of the olefin polymerization catalyst spherical carrier Z1 is relatively regular, the surface is smooth, and it is basically spherical. The particle size distribution is relatively concentrated, and there are basically no irregular particles.

[0114] According to GC-MS, elemental analysis and NMR characterization, the structural formula of Z1 is:

[0115]

[0116] In a 2.5L glass reaction bottle, add 500mL of titanium tetrachloride, cool to -20°C, add 40g of the olefin polymerization catalyst spherical carrier Z1 obtained in Preparation Example 1, and stir at -20°C for 30min. Then, slowly heat up to 110°C, add 7.5mL of diethyl 2,3-diisopropyl-2-cyanosuccinate during the heating process, maintain at 110°C for 30min, and filter out the liquid. Then, add titanium tetrachloride and wash twice, and finally wash three times with hexane, and dry to obtain olefin polymerization catalyst A-3.

[0117] Preparation Example 4

[0118] In a 2L reactor, add 40g (0.4mol) of magnesium chloride, 280mL (4.8mol) of ethanol, 5g of ethyl acetate, and 5g of PVP (polyvinylpyrrolidone) as surfactants, heat to 90°C with stirring, react at this temperature for 2 hours, then add 1.6mol of epichlorohydrin, continue to react at this temperature at 90°C for half an hour, then filter press, wash the filtered product with toluene 8 times, and finally dry the product in vacuum to obtain a spherical catalyst carrier Z2 for olefin polymerization.

[0119] The average particle diameter (D50) of the olefin polymerization catalyst spherical carrier Z2 is 50 microns, and the particle size distribution ((D90-D10) / D50) is 1.0. The particle morphology of the olefin polymerization catalyst spherical carrier Z2 is relatively regular, the surface is smooth, and it is basically spherical. The particle size distribution is relatively concentrated, and there are basically no irregular particles.

[0120] According to GC-MS, elemental analysis and NMR characterization, the structural formula of Z2 is:

[0121]

[0122] In a 2.5L glass reaction bottle, add 500mL of titanium tetrachloride, cool to -20°C, add 40g of the olefin polymerization catalyst spherical carrier Z2 obtained in Preparation Example 2, and stir at -20°C for 30min. Then, slowly heat up to 110°C, add 7.5mL of diethyl 2,3-diisopropyl-2-cyanosuccinate during the heating process, maintain at 110°C for 30min, and filter out the liquid. Then, add titanium tetrachloride and wash twice, and finally wash three times with hexane, and dry to obtain olefin polymerization catalyst A-4.

[0123] The following examples are used to illustrate the solid catalyst component and its preparation method and the method for olefin polymerization of the present invention.

[0124] Example 1

[0125] (1) Preparation of solid catalyst component

[0126] In a 5L autoclave, 1.1L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 25.0g catalyst component A-1 were added, and the reaction was carried out at 22°C for 10 minutes; then 10g propylene was added, and the reaction was carried out at 20°C for 10 minutes, and the unreacted propylene was vented; the reactor was replaced with nitrogen, hydrogen was added to the reaction pressure of 0.2MPa, and the reaction was carried out at 15°C for 10 minutes, and the unreacted hydrogen was vented. After filtering the liquid in the reaction product, it was dried under vacuum (temperature 45°C, time 40min) to obtain a solid catalyst component, which was recorded as E-1. The composition of the catalyst component E-1 is as follows: 3.2% by weight of titanium, 15.6% by weight of magnesium, 55.0% by weight of chlorine, 9.8% by weight of diethyl 2,3-diisopropyl-2-cyanosuccinate and 7.8% by weight of polyolefin.

[0127] (2) Propylene polymerization A

[0128] In a 5L autoclave, 1.3mmol triethylaluminum, 0.05mmol cyclohexylmethyldimethoxysilane, 10mL hexane and 15mg solid catalyst component E-1 were added, and after 1.5NL of hydrogen was introduced, 2.0L liquid propylene was added; the temperature was raised to 70°C while stirring and polymerization reaction was carried out at 70°C for 1 hour; stirring was stopped, and unpolymerized propylene monomer was removed to obtain polypropylene, which was recorded as P-1A.

[0129] Propylene Polymerization B

[0130] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-1B.

[0131] Example 2

[0132] (1) Preparation of solid catalyst component

[0133] In a 5L autoclave, 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 25.0g catalyst component A-2 were added and reacted at 15°C for 10 minutes; then 12g propylene was added, reacted at 25°C for 10 minutes, and the unreacted propylene was vented; the reactor was replaced with nitrogen, hydrogen was added to the reaction pressure of 0.2MPa, reacted at 20°C for 10 minutes, and the unreacted hydrogen was vented. After filtering out the liquid in the reaction product, it was dried under vacuum to obtain a solid catalyst component, recorded as E-2. The composition of the catalyst component E-2 is as follows: 3.1% by weight of titanium, 16.1% by weight of magnesium, 48.6% by weight of chlorine, 6.8% by weight of diethyl 2,3-diisopropyl-2-cyanosuccinate and 19.8% by weight of polyolefin.

[0134] (2) Propylene polymerization A

[0135] Polypropylene was obtained by polymerization according to the method of propylene polymerization A in Example 1, except that E-2 was used instead of E-1, and polypropylene was obtained, which was recorded as P-2A.

[0136] Propylene Polymerization B

[0137] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-2B.

[0138] Example 3

[0139] (1) Preparation of solid catalyst component

[0140] In a 5L autoclave, 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 25.0g catalyst component A-2 were added and reacted at 15°C for 10 minutes; then 12g ethylene was added, reacted at 30°C for 10 minutes, and unreacted propylene was vented; the reactor was replaced with nitrogen, hydrogen was added to the reaction pressure of 0.2MPa, reacted at 25°C for 10 minutes, and unreacted hydrogen was vented. After filtering out the liquid in the reaction product, it was dried under vacuum to obtain a solid catalyst component, recorded as E-3. The composition of catalyst component E-3 is as follows: 2.0% by weight of titanium, 14.8% by weight of magnesium, 45.6% by weight of chlorine, 5.7% by weight of diethyl 2,3-diisopropyl-2-cyanosuccinate and 22.3% by weight of polyolefin.

[0141] (2) Propylene polymerization A

[0142] Polypropylene was obtained by polymerization according to the method of propylene polymerization A in Example 1, except that E-3 was used instead of E-1, and the polypropylene was recorded as P-3A.

[0143] Propylene Polymerization B

[0144] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-3B.

[0145] Comparative Example 1

[0146] Propylene Polymerization A

[0147] The method of propylene polymerization A and B in Example 1 was followed, except that catalyst component A-1 was used instead of E-1 to obtain polypropylene, which was recorded as CP-1A and CP-1B.

[0148] Comparative Example 2

[0149] Propylene Polymerization A

[0150] The method of propylene polymerization A and B in Example 2 was followed, except that catalyst component A-2 was used instead of E-2 to obtain polypropylene, which was recorded as CP-2A and CP-2B.

[0151] Comparative Example 3

[0152] The method of Preparation Example 1 was followed, except that 2,4-pentanediol dibenzoate was used instead of diethyl 2,3-diisopropyl-2-cyanosuccinate, to obtain a catalyst component, which was recorded as 2A-1.

[0153] According to the method for preparing the catalyst in Example 1, a catalyst component was obtained and recorded as 2E-1.

[0154] The method of propylene polymerization A and B in Example 1 was followed, except that 2A-1 and 2E-1 were used instead of E-1, to obtain polypropylene, which were recorded as 2PA-1A and 2PA-1B, 2PE-1A and 2PE-1B.

[0155] Table 1 Propylene polymerization results

[0156]

[0157]

[0158] It can be seen that when the diol ester compound is used as the internal electron donor, the molecular weight distribution of the prepolymerized catalyst does not change significantly compared with the catalyst without prepolymerization.

[0159] Example 4

[0160] (1) Preparation of solid catalyst component

[0161] In a 5L autoclave, add 1.1L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-3, react at 22°C for 10 minutes; then add 10g propylene, react at 20°C for 10 minutes, and vent the unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 15°C for 10 minutes, and vent the unreacted hydrogen. After filtering off the liquid in the reaction product, dry it under vacuum (temperature 45°C, time 40min) to obtain a solid catalyst component, recorded as E-4.

[0162] (2) Propylene polymerization A

[0163] In a 5L autoclave, 1.3mmol triethylaluminum, 0.05mmol cyclohexylmethyldimethoxysilane, 10mL hexane and 15mg solid catalyst component E-4 were added, and after 1.5NL of hydrogen was introduced, 2.0L liquid propylene was added; the temperature was raised to 70°C under stirring and polymerization reaction was carried out at 70°C for 1 hour; stirring was stopped, and unpolymerized propylene monomer was removed to obtain polypropylene, which was recorded as P-4A.

[0164] Propylene Polymerization B

[0165] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-4B.

[0166] Example 5

[0167] (1) Preparation of solid catalyst component

[0168] In a 5L autoclave, add 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-4, react at 15°C for 10 minutes; then add 12g propylene, react at 25°C for 10 minutes, and vent the unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 20°C for 10 minutes, and vent the unreacted hydrogen. After filtering out the liquid in the reaction product, dry it under vacuum to obtain a solid catalyst component, recorded as E-5.

[0169] (2) Propylene polymerization A

[0170] Polypropylene was obtained by polymerization according to the method of propylene polymerization A in Example 4, using E-5 instead of E-1, and recorded as P-5A.

[0171] Propylene Polymerization B

[0172] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-5B.

[0173] Example 6

[0174] (1) Preparation of solid catalyst component

[0175] In a 5L autoclave, add 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-4, react at 15°C for 10 minutes; then add 12g ethylene, react at 30°C for 10 minutes, and vent unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 25°C for 10 minutes, and vent unreacted hydrogen. After filtering out the liquid in the reaction product, dry it under vacuum to obtain a solid catalyst component, recorded as E-6.

[0176] (2) Propylene polymerization A

[0177] Polymerization was carried out according to the method of propylene polymerization A in Example 4, except that E-6 was used instead of E-1 to obtain polypropylene, which was recorded as P-3A.

[0178] Propylene Polymerization B

[0179] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-6B.

[0180] Comparative Example 4

[0181] Propylene Polymerization A

[0182] The method of propylene polymerization A and B in Example 4 was followed, except that catalyst component A-3 was used instead of E-4 to obtain polypropylenes, which were designated as CP-4A and CP-4B.

[0183] Comparative Example 5

[0184] Propylene Polymerization A

[0185] The method of propylene polymerization A and B in Example 5 was followed, except that catalyst component A-4 was used instead of E-5 to obtain polypropylenes, which were designated as CP-5A and CP-5B.

[0186] Table 2 Propylene polymerization results

[0187]

[0188] It can be seen that the solid catalyst component of the present invention is used for olefin polymerization, and compared with the existing prepolymerization catalyst technology, such as compared with the comparative example, the catalyst hydrogen adjustment sensitivity is significantly improved, and the molecular weight distribution of the propylene polymer is significantly broadened, which is more conducive to improving the processing performance of the product.

[0189] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0190] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A catalyst component for olefin polymerization, characterized in that The catalyst components include magnesium, titanium, halogen, poly-α-olefin and internal electron donor compound; the internal electron donor compound includes the compound represented by formula (I); In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; Wherein, the R'1 and R'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl or aralkyl groups are optionally replaced by other atoms.

2. The catalyst component according to claim 1, characterized in that The poly-α-olefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene and polyisoprene; And / or, based on the total weight of the catalyst component, the content of magnesium in the catalyst component is 1% to 18% by weight, the content of titanium is 0.1% to 3.5% by weight, the content of halogen is 2% to 65% by weight, the content of poly-α-olefin is 0.1% to 89% by weight, and the content of internal electron donor compound is 0.6% to 15% by weight; Preferably, based on the total weight of the catalyst component, the content of the poly-α-olefin is 1 wt% to 50 wt%, the content of the titanium element is 0.5 wt% to 2.5 wt%, the content of the magnesium element is 1 wt% to 16 wt%, the content of the halogen is 2 wt% to 55 wt%, and the content of the internal electron donor compound is 1 wt% to 10 wt%; Further preferably, based on the total weight of the catalyst component, the content of the poly-α-olefin is 9.5 wt% to 35 wt%, the content of the titanium element is 1.5 wt% to 2.5 wt%, the content of the magnesium element is 11 wt% to 16 wt%, the content of the halogen is 40 wt% to 55 wt%, and the content of the internal electron donor compound is 8 wt% to 10 wt%; and / or, the catalyst component is a spherical solid particle; and / or, the average particle size D of the catalyst component 50 It is 5 to 150 μm, preferably 20 to 80 μm.

3. The catalyst component according to claim 1 or 2, characterized in that The magnesium element comes from alkoxy magnesium, spherical magnesium chloride alcoholate or spherical magnesium compound; Preferably, the general formula of the magnesium alkoxide is Mg(OEt) 2-k-l (OEH) k (OiPr) l , wherein Et is ethyl, EH is 2-ethylhexyl, iPr is isopropyl, and k and l are each independently 0 to 0.5; Preferably, the general formula of the spherical magnesium chloride alcoholate is Mg(R′OH) i (H2O) j , wherein R′ is methyl, ethyl, n-propyl or isopropyl, i is 1.5 to 3.5, and j is 0 to 0.1; Preferably, the general formula of the spherical magnesium compound is as shown in formula (II): In formula (II), R1 is C1~C 12 R2 and R3 are the same or different and are hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen; m is 0.1-1.9; n is 0.1-1.9; m+n=2.

4. A method for preparing a catalyst component for olefin polymerization, characterized in that: include: (1) in the presence of an inert solvent, allowing the catalyst component A, alkyl aluminum and an external electron donor compound to contact and react; The catalyst component A contains titanium, magnesium, halogen and an internal electron donor compound; the internal electron donor compound includes a compound represented by formula (I); In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; Wherein, the R"'1 and R"'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen on the aromatic ring in the aryl, alkylaryl or aralkyl group is optionally replaced by other atoms; (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction; (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

5. The preparation method according to claim 4, characterized in that: The α-olefin is selected from one or more of ethylene, propylene, butene, octene and isopentene; and / or, the mass ratio of the α-olefin to the catalyst component A is 0.04:1 to 10:1; And / or, the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01-1.0 MPa, preferably 0.1-0.5 MPa, more preferably 0.2-0.3 MPa.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the contact reaction conditions include: temperature of 0 to 30°C, preferably 15 to 25°C; time of 1 to 30 min, preferably 10 to 20 min; And / or, the conditions of the polymerization reaction in step (2) include: temperature of 0 to 50° C., preferably 15 to 25° C.; time of 5 to 30 min, preferably 10 to 20 min; And / or, the reaction conditions in step (3) include: temperature of 0 to 50° C., preferably 15 to 25° C.; time of 5 to 30 min, preferably 10 to 20 min.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The magnesium element comes from alkoxy magnesium, spherical magnesium chloride alcoholate or spherical magnesium compound; Preferably, the general formula of the magnesium alkoxide is Mg(OEt) 2-k-l (OEH) k (OiPr) l , wherein Et is ethyl, EH is 2-ethylhexyl, iPr is isopropyl, and k and l are 0 to 0.5; Preferably, the general formula of the spherical magnesium chloride alcoholate is Mg(R′OH) i (H2O) j , wherein R′ is methyl, ethyl, n-propyl or isopropyl, i is 1.5 to 3.5, and j is 0 to 0.1; Preferably, the general formula of the spherical magnesium compound is as shown in formula (II): In formula (II), R1 is C1~C 12 R2 and R3 are the same or different and are hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen; m is 0.1-1.9; n is 0.1-1.9; m+n=2.

8. A catalyst component prepared according to the preparation method according to any one of claims 4 to 7.

9. A catalyst for olefin polymerization, characterized in that: The catalyst comprises a catalyst component, an alkyl aluminum and optionally an external electron donor compound or a reaction product thereof; The catalyst component is at least one selected from the catalyst component described in any one of claims 1 to 3 and the catalyst component prepared by the preparation method described in any one of claims 4 to 7.

10. A method for olefin polymerization, characterized in that: The method comprises: subjecting olefin to polymerization reaction in the presence of the catalyst for olefin polymerization according to claim 9; Preferably, the general formula of the olefin is CH2=CHR, R is hydrogen, C1-C6 alkyl or C6-C 10 The aromatic group; Preferably, the polymerization reaction temperature is 0 to 150°C, preferably 60 to 90°C.

Citation Information

Patent Citations

  • A spherical carrier for olefin polymerization catalyst and preparation method thereof

    CN104558281B

  • A solid composition, its preparation method and application

    CN104558283B

  • Catalyst component used for olefin polymerization and preparation method thereof as well as catalyst used for olefin polymerization and application

    CN104558284A

  • Globular catalyst component used for olefine polymerization and its catalyst

    CN1289542C

  • Magnesium halide / alcohol addition compound and its preparing method and use

    CN1580136A